2018
DOI: 10.1038/s41598-018-31966-6
|View full text |Cite
|
Sign up to set email alerts
|

Solid-state random microlasers fabricated via femtosecond laser writing

Abstract: Here we demonstrate resonant random lasing in Rhodamine B-doped polymeric microstructures fabricated by means of femtosecond laser writing via two-photon polymerization. To the best of our knowledge, this is the first demonstration of random lasing action in on-chip microdevices. Their feedback mechanism relies on diffuse reflections at the structure sidewall surfaces, which is known as spatially localized feedback since the scattering centers lie over the edges of the gain medium. By exciting the structures w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Generally speaking, scattering is detrimental to laser action because it induces loss to the DFB polymer lasers. However, the combination of multiple scattering and high gain leads to random laser action [17,18,19,20,21,22]. So, simultaneous DFB lasing and random lasing are expected in one single integrated device if the scattering particles are introduced appropriately into the DFB cavity, which forms a periodic-random compound cavity.…”
Section: Introductionmentioning
confidence: 99%
“…Generally speaking, scattering is detrimental to laser action because it induces loss to the DFB polymer lasers. However, the combination of multiple scattering and high gain leads to random laser action [17,18,19,20,21,22]. So, simultaneous DFB lasing and random lasing are expected in one single integrated device if the scattering particles are introduced appropriately into the DFB cavity, which forms a periodic-random compound cavity.…”
Section: Introductionmentioning
confidence: 99%
“…For specular reflection‐based cavities, the free spectral range (FSR) is the distance between the two consecutive lasing peaks that remains constant in the spectrum. [ 29 ] Here, the FSR values for 26.6 µm‐length cavity showed a significant random variation of 1.85, 1.26, 1.56, 1.26, 1.34, 1.18, 1.81, and 1.64 nm indicating diffuse reflection‐based resonant oscillations.…”
Section: Resultsmentioning
confidence: 81%
“…This close-loop formation can be only possible if we assume there are diffuse reflections at the edge of the microcrack. This assumption is reasonable because the sidewalls of the microcrack are rough and this phenomenon has been proposed previously in microstructures enabled by direct laser writing [41]. It is suggested that more studies including finite-difference time-domain simulation and PL mapping are needed to find the exact lasing mechanism.…”
Section: Lasing Emission From a Single Microcrackmentioning
confidence: 83%